1999–2001 Cancer Mortality Rates for Asian and Pacific Islander Ethnic Groups with Comparisons to Their 1988–1992 Rates - Chu, Kenneth C. (2005)
We report upper and lower boundary estimates of the 1999–2001 site-specific cancer mortality rates for Asian Indians, Chinese, Filipinos, Koreans, Vietnamese, Native Hawaiians, and Samoans. These rates are for the seven states (California, Hawaii, Illinois, New Jersey, New York, Texas, and Washington) that officially record mortality data for these ethnicities. The rates are based on the 2000 Census, which reports two population counts as follows: persons who identify themselves as belonging to a single ethnic group (which forms the basis for an upper boundary estimate of the rates) and persons who identify themselves as belonging to a single ethnic group or to multiple groups that include the single ethnic group (which forms the basis for a lower boundary estimate for the rates). The top five cancers for each Asian and Pacific Islander ethnic group by gender are reported. In addition, the 1988–1992 cancer mortality rates based on the 1990 Census for Chinese, Filipino, Japanese, and Native Hawaiians are determined. Their 1999–2001 and 1988–1992 rates are compared.